2008
DOI: 10.1097/olq.0b013e31816f1c65
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Routine, Occupation-Based Gonorrhea and Syphilis Screening Program in Moscow, Russia: An Analysis of Sexually Transmitted Infection Prevalence and Cost-Effectiveness

Abstract: Modifications to occupation-based screening, including an increased focus on higher risk population and the adoption of more current diagnostic technologies, could help to use prevention resources more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Overall, STI prevalence among non-IDUs was comparable to the STI prevalence from the general population in St. Petersburg [52,53], and STI prevalence among IDUs in this study was similar to the prevalence found among IDUs in other countries [54,55]. The low STI prevalence might reflect a trend of reduced STIs being reported over the years in Russia [56-58].…”
Section: Discussionsupporting
confidence: 78%
“…Overall, STI prevalence among non-IDUs was comparable to the STI prevalence from the general population in St. Petersburg [52,53], and STI prevalence among IDUs in this study was similar to the prevalence found among IDUs in other countries [54,55]. The low STI prevalence might reflect a trend of reduced STIs being reported over the years in Russia [56-58].…”
Section: Discussionsupporting
confidence: 78%
“…After reviewing the full articles, one article was excluded because it was not on Russia [35] and three were excluded because they were not original economic analyses. [1,36,37] The study's final sample consisted of 16 economic studies that satisfied our inclusion criteria ( Figure 1, Table 1 [4][5][6]9,[38][39][40][41][42][43][44][45][46][47][48][49] ).…”
Section: Resultsmentioning
confidence: 99%
“…[4,44,47] Economic analysis was the primary objective in 15 (93.8%) studies. Seven articles were on pharmaceuticals, three were on services, [42][43][44] three were on health technologies, [38,45,48] and three did not specify any primary health intervention. [9,40,41] Treatment (n = 8, 50%), and prevention and screening (n = 4, 25%) were the most investigated medical functions.…”
Section: Extent and Trend Of Health Economics Studiesmentioning
confidence: 99%
“…[27] The global prevalence rate of syphilis has again surged because of multiple biological and social factors. [11282930] To date, syphilis has imposed considerable health and economic burden on many countries, especially the developing countries. [293132]…”
Section: Discussionmentioning
confidence: 99%